Clinical profile of patients with pleural effusion admitted to KMCTH - Dhital, KR; Acharya, R; Bhandari, R; Kharel, P; Giri, KP; Tamrakar, R (Kathmandu University Medical Journal, 2010)
Background: pleural effusion is the common findings in patients presenting with cardiopulmonary symptoms but specific studies are lacking in Nepal. Objective: The main objective of this study is to find out the various causes of pleural effusion, their mode of clinical presentation and laboratory analysis of blood and pleural fluid to aid diagnosis of patients with pleural effusion. Materials and methods: Retrospective data from July 2009 to July 2007 from all the cases diagnosed with pleural effusion were taken. Altogether 100 cases diagnosed with pleural effusion by chest X-ray (Posterior- Anterior and Lateral view) and Ultrasonogram of the chest were studied. The following parameters were analysed: Patients demographic profile, causes, location (Unilateral, Bilateral), Blood haemoglobin and count, sputum profile, Monteux test, chest Xray and USG findings and pleural fluid analysis[Biochemical, Haematological, Microbiological(culture and stain) and cytological]. This study was analysed by using SPSS 16. Results: The mean age of the patient was 44.89 ± 21.59 and must patients with pleural effusion belong to age group 21- 30. Most common cause of pleural effusion was found to be tubercular effusion followed by parapneumonic effusion. Right sided effusion was seen in most cases of tubercular parapneumonic and malignant effusion whereas bilateral effusion was seen in 87.5% of the patient (7 out of 8) having congestive heart failure and all cases of renal disease (4 out of 4). Shortness of breath (83%), cough (67%) and fever (66%) are the most common mode of clinical presentation. Conclusion: Our study concluded that the most common cause of unilateral pleural effusion is tuberculosis followed by parapneumonic effusion and most cases of those belong to younger age group (21 -30yrs) and most common cause of bilateral pleural effusion is congestive cardiac failure. Key words: Pleural effusion; Tuberculosis; pneumonia; malignancy; protein; ADA DOI: 10.3126/kumj.v7i4.2772 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 438-444